ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIVITAS INSPEKTORAT JENDERAL KEMENTERIAN DALAM NEGERI DALAM PENGAWASAN PENYELENGGARAAN PEMERINTAHAN DAERAH - Abel Rizky Siregar; Roy Valiant Salomo (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2020)
This study aims to analyze the factors affecting the effectiveness of the Inspectorate General of the Ministry of Home Affairs in the supervision of the administration of local governance. This research uses the post-positivism paradigm with qualitative research methods. In-depth interviews and document studies were conducted to obtain the necessary data and information. The results of this study explain that the factors affecting the effectiveness of the Inspectorate General of the Ministry of Home Affairs in supervision the administration of local governance include structure, systems, strategy, style, staff, skills, and shared values. This is certainly by the elements contained in the 7S Mckinsey model that researchers use as a knife analysis in answering research questions. The results of the analysis revealed that the institutional structure was not yet matched, the still weak laws and regulations related to the supervision of the regional government, business processes were running well but the use of information technology was needed in building the supervision system, there was a need to strengthen planning to meet the needs of APIP to be met both in terms of the number and competence as well as the leadership style of the highest leadership is very participatory, democratic and can certainly support the development of existing work culture to increase the effectiveness of the Inspectorate General of the Ministry of Home Affairs in supervision the administration of local governance. Keywords: effectiveness, supervision, the administration of local governanc